ANALISIS EFEKTIVITAS PENGELOLAAN DANA DESA DI DESA EHO ORAHILI FAU KECAMATAN FANAYAMA KABUPATEN NIAS SELATAN - Maduwu, Lusia Siska (LPPM Universitas Nias Raya, 2022)
The purpose of this study is to explain the effectiveness of village fund management in Eho Orahili Village of Fanayama District of South Nias Regency in 2018-2020. The type of research used is qualitative type. The data source is the village fund report for 2018-2020. The data collection technique is the village fund report. The data analysis method used is data reduction analysis, data display, conclusion or ferivikasi. The results of this study show that in 2018 and 2019 the management of the use of village funds has been effective in accordance with the planning of the implementation of village fund management for the construction of trenches, the construction of highways has been in accordance with the applicable rules as affirmed in the Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration of the Republic of Indonesia Number 05 of 2015 concerning the Determination of Priorities for the Use of Village Funds in 2015 Article 8 letter (a) that the priority The use of village funds can include the construction and maintenance of village roads.